EVALUATION OF ANTIBACTERIAL, ANTIOXIDANT, AND ANTICANCER POTENTIALS FROM MARINE RED ALGAE GRACILARIA CORTICATA - P, Jayasree; R, Thiruchelvi; P, Balashanmugam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was to evaluate the biological activity of Red algae, Gracilaria corticata, collected from the southeast coast of Mandapam, Ramanathapuram, Tamil Nadu. Seaweeds are rich in bioactive compounds. Seaweeds are highly diverse group of organism from secondary metabolites of the natural source are a potential source. The marine seaweed is the interesting group of their broad spectrum of biological activities such as antibacterial, antioxidant, and anticancer. Methods: The antibacterial activity of G. corticata was tested against Staphylococcus aureus and Escherichia coli by disk diffusion method. In vitro antioxidant activity was determined by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay. 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide assay was employed to study the anticancer activity against (MDA-MB 231) human breast cancer cell line. Results: The DPPH assay screening of methanolic extract of G. corticata showed specific activity of inhibition. In antibacterial shows the growth of two virulent strains of pathogenic bacteria, E. coli and Bacillus subtilis. In anticancer activity obtained results indicated that the methanol extracts of G. corticata were cytotoxic against (MDA-MB231) human breast cancer cell. Conclusion: These results show that G. corticata has a great biological potential, which could be considered for future uses in pharmaceutical, food, and cosmetics purpose.